Second primary tumors in patients with a head and neck paraganglioma. Issue 9 (25th June 2019) - Contrera, Kevin J.; Yong, Valeda; Reddy, Chandana A.; Berber, Eren; Lorenz, Robert R.
Abstract: Background: There are conflicting recommendations and possibly overuse of imaging for surveillance of second primary tumors for patients with a history of head and neck paraganglioma. Methods: Retrospective cohort study of 234 adults with head and neck paragangliomas (1990‐2010) followed for a mean of 7.5 ± 8.4 years. Results: The rate of second paraganglioma was 1.7% after 5 years and 5.1% after 10 years, yielding an incidence of 6.65 per 1000 person‐years. Only 1.3% of patients (2.59 per 1000 person‐years) ever had a second paraganglioma in the chest, abdomen, or pelvis. Patients with a hereditary paraganglioma (hazard ratio [HR] = 4.84, 95% confidence interval [CI]: 1.52‐15.43) or carotid body tumor (HR = 3.55, 95% CI: 1.15‐10.99) were at greater risk. Conclusions: The incidence rate of a second primary paragangliomas is low but increases with hereditary disease. These results question the utility of repeated imaging outside of the neck to screen for second paragangliomas.